Improvement Of Social Literacy Skills And Learning Interest Through The Method Of Play Using Flipbook Media - Dian Susilowati; Muhammad Hanif; Sudarmiani Sudarmiani (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to improve students' social literacy and learning interest through the implementation of play methods assisted by flipbook media in Group B at Rahmatan Lil Alamin Islamic Kindergarten, Madiun City. This classroom action research employed Kemmis and McTaggart's spiral model, conducted in two cycles with 19 children as research subjects. Problem identification showed that only 12% of students achieved the Very Well Developed (BSB) category in social literacy at the pre-cycle stage. Data were collected through triangulation using observation sheets and picture questionnaires with assessment rubrics on a scale of 1-4 referring to early childhood education assessment criteria. The success criterion was set at 80% of students achieving at least the Developing as Expected (BSH) category. The results showed significant improvement in social literacy from 37% (pre-cycle) to 65% (cycle I) and 88% (cycle II), with a total increase of 51%. Learning interest increased from 37% to 62% (cycle I) and 82% (cycle II), with a total increase of 45%. Key modifications in cycle II, including transforming flipbooks into game-based learning and implementing sociodramatic play, proved effective in increasing active participation and internalisation of social values. This study concludes that the synergy between play methods and interactive flipbook media can transform passive learning environments into dynamic and motivating interaction spaces for early childhood